Nanostructured Triblock Copolymers with Chemically Complementary Components and Their Ionic Conductivity - Zheltonozhskaya, Tatyana; Shembel, Elena; Fedorchuk, Sergey; Kunitskaya, Larisa; Maksyuta, Iryna; Permyakova, Nataliya; Gomza, Yuriy (Journal of Research Updates in Polymer Science, 2013)
A series of structural and electrochemical studies of the triblock copolymers (TBCs) based on poly(ethylene oxide) (Mn = 14 and 35 kDa) and polyacrylamide (PAAm-b-PEO-b-PAAm), which formed the intramolecular polycomplexes, were carried out using nuclear magnetic resonance, differential scanning calorimetry, wide-angle and small-angle X-ray scattering, and impedance spectroscopy. The combination of the amorphous mass-fractal-organized structure of the copolymers with high level of the ionic conductivity of pure TBCs and their compositions with the couple KI/I2 and LiPF6 salt was established. Possible reasons for the effects in the context of applications of TBC compositions in solar cells and lithium batteries are discussed.